The application of market appeal-robusticity matrix as a tool for cultural heritage and tourism management (case study : Melaka historic city) - Era Triana, Era Triana (2005)
Tourism carrying capacity refers to the concept of preserving and maintaining an area or asset in its original state, taking into consideration the ability and capability of resources to withstand the effects of tourist activities. The city of Melaka is cultural tourism destination heritage that has attracted local and foreign tourist. The city of Melaka is a destination that serves various roles and functions. The aim of this research is to evaluate the development of tourism in Melaka, and assess the impact of tourism activities on the tourism carrying capacity. This study will also determine the balance between the cultural heritage management and cultural tourism to plan a tourism management technique. The Market Appeal – Robusticity Matrix Method was used as a method based on the indicators that have been identified which can contribute to the development of tourism cultural heritage. The indicators consist of aspects, such as fragility or robustness of asset, product promotion, activity, aesthetic value, history, facilities availability and accessibility. It also involves education and tourism management system from the government and NGOs. The result of this study identified the cultural tourism asset that has a great potential for development based on the carrying capacity according to certain levels (A1, A2, C1, C2 and D1). Recommendations are given including the tourism management technique, the management carrying capacity, tourism promotion, policies, guidelines and strategies.